Length‐weight relationships of three fish species from Beibu Gulf in China. (20th August 2018) - Li, Yuan; Feng, Ji; Song, Puqing; Zhang, Ran; Li, Hai; Lin, Longshan
Abstract: The length–weight relationships (LWRs) were analyzed for three fish species collected from Beibu Gulf between October 2012 and March 2013. The study used bottom trawl with 40 mm mesh size. The values of parameter b varied from 2.8495 to 3.0277 .